Constituting practices, shaping markets: remaking healthy living through commercial promotion of blood pressure monitors and scales. Issue 1 (1st January 2020) - Williams, Rosalind; Weiner, Kate; Henwood, Flis; Will, Catherine
ABSTRACT: Commercial actors play a key role in promoting public health agendas as they move into space previously occupied by the state-sponsored health sector and welfare state. This paper examines how marketing of digital self-monitoring devices promotes public health. Existing self-monitoring research often separates or compares positions of commercial actors and users, using a discourse lens to examine commercial actors' 'expectations' and 'promises', and user research focusing on 'practices'. The research on which this paper is based moves beyond this divide, examining commercial and user worlds through a practice lens. We draw on the research's first stage which examined self-monitoring device marketing, arguing that marketing can be understood as constituting self-monitoring practices. Much literature on self-monitoring focuses on novel networked devices, resulting in potential over-emphasis on change and innovation. Taking cases of well-established bodily monitoring (weighing and blood pressure), we set self-monitoring within a longer history. We draw on Shove's practice theory which attends to histories of practices and evolutions in practices required elements materials, meanings and competences. Commercial companies are shown to rework well-embedded practices as they constitute the practice elements of self-monitoring. They thus keep in play continuities and novelty, maintaining connections to health while moving away from clinical associations. We argue that, in constituting self-monitoring practices as 'aesthetic', 'enjoyable', and 'shared', commercial actors address implicit resistances to negative connotations of 'individualised', 'responsibilised' consumer citizens implied in neo-liberal health-promotion agendas, widening the self-monitoring market and promoting public health by creating more desirable 'lifestyle' practices.